2017
DOI: 10.14704/nq.2017.15.2.1067
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Feedback Training For Overweight Women: Improvement of Food Craving And Mental Health

Abstract: Major risk factors for diabetes, cardiovascular disorders and cancer (prostate, intestine, breast, etc.) are obesity and being overweight. This study aims to investigating the effect of neurofeedback training to food craving and mental health in overweight women. To this aim, thirty overweight women were divided into two groups; neurofeedback and control groups, using a simple random method. In this experiment, which was accompanied with pre-test and post-test with the control group, women in the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Of the controlled studies, six ESs were categorized to vivo cue exposure, 39 studies to cognitive regulation strategies (n = 6 acceptance, n = 13 reappraisal, n = 7 suppression, and n = 13 distraction), 13 studies to cognitive control training (n = 3 ICT, n = 4 AAT, and n = 6 ABM), and six to neurofeedback or biofeedback interventions …”
Section: Resultsmentioning
confidence: 99%
“…Of the controlled studies, six ESs were categorized to vivo cue exposure, 39 studies to cognitive regulation strategies (n = 6 acceptance, n = 13 reappraisal, n = 7 suppression, and n = 13 distraction), 13 studies to cognitive control training (n = 3 ICT, n = 4 AAT, and n = 6 ABM), and six to neurofeedback or biofeedback interventions …”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, it is well established that poor eating habits in this age group are directly linked to the emergence of some subsequent health problems in the future, such as overweight, hyperlipidemia, and diabetes (Franko et al, 2008). However, obesity and overweight are among the risk factors for the development and spread of chronic diseases (Long and Stevens, 2004;Fattahi et al, 2017), and these diseases, due to high health costs, bring a heavy economic burden on countries. For example, research has shown that only for type 2 diabetes, which is associated with poor physical activity and inappropriate nutrition, the total cost of the disease worldwide is more than $132 billion a year, and it is estimated that these costs will increase to $156 billion by 2010 and rise to $192 billion by 2030 (Brunner and Suddarth, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mean number of sessions per study was 7.42 (range 1–12). Among reviewed article, three studies were focused on non-clinical samples [ 55 , 56 , 57 ], two on subthreshold samples [ 58 , 59 ], two on adolescents with AN [ 60 , 61 ], two on patients with RD [ 62 , 63 ] and 5 on overweight/obese individuals [ 61 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%